The determinants of income inequality evidence from developing Asia / Nurin Jazlina Abdul Hadi - Abdul Hadi, Nurin Jazlina (2019)
This study is about the determinants of income inequality. There are seven developing Asia countries has been chosen as the case of this study. The scope of study is accounted for 30 years from 1987 until 2016 using panel data. There are several variables were chosen as indicator which are foreign direct investment, gross domestic product, government expenditure and trade. Optimal model selection procedure, together with data panel analysis technique is used to determine the most optimal model to explain the determinants of income inequality. The findings of this paper indicate that the foreign direct investment are influenced by income inequality dependent variable. In conclusion, this study rejects the null hypothesis since it shows that foreign direct investment does have a significant relationship towards income inequality.